Dysfunctional Attitudes and Affective Responses to Daily Stressors: Separating Cognitive, Genetic, and Clinical Influences on Stress Reactivity - Conway, Christopher C. (Cognit Ther Res, 2014)
Despite decades of research examining diathesis-stress models of emotional disorders, it remains unclear whether dysfunctional attitudes interact with stressful experiences to shape affect on a daily basis and, if so, how clinical and genetic factors influence these associations. To address these issues, we conducted a multi-level daily diary study that examined how dysfunctional attitudes and stressful events relate to daily fluctuations in negative and positive affect in 104 young adults. Given evidence that clinical and genetic factors underlie stress sensitivity, we also examined how daily affect is influenced by internalizing and externalizing symptoms and brain-derived neurotrophic factor (BDNF) genotype, which have been shown to influence neural, endocrine, and affective responses to stress. In multivariate models, internalizing symptoms and BDNF Val66Met genotype independently predicted heightened negative affect on stressful days, but dysfunctional attitudes did not. Specifically, the BDNF Met allele and elevated baseline internalizing symptomatology predicted greater increases in negative affect in stressful circumstances. These data are the first to demonstrate that BDNF genotype and stress are jointly associated with daily fluctuations in negative affect, and they challenge the assumption that maladaptive beliefs play a strong independent role in determining affective responses to everyday stressors. The results may thus inform the development of new multi-level theories of psychopathology and guide future research on predictors of affective lability.